Methods of Teaching Technical Mechanics in the Field of Technological Education - Solieva Gulkhayo Khoshimjon kizi; Аbdukarimova Nazokat Аbdukholik kizi (Periodica Journal, 2022)
In this article, wood carving has been developed in Central Asia since ancient times and has been widely used in the manufacture of household utensils. This carving has been used to decorate doors, gates, columns, various beams, tables, chairs, tables, boxes, frames, pencils and other items of ancient architecture. The works created by the people practically amaze people with their subtlety, complexity and naturalness. Opinions and comments on the methodology of teaching the subject of technical mechanics in the field of technological education.
Keywords: Technical mechanics; technological education; style; wood